Effect of Fatigue Training on Safety, Fatigue, and Sleep in Emergency Medical Services Personnel and Other Shift Workers: A Systematic Review and Meta-Analysis. (15th February 2018) - Barger, Laura K.; Runyon, Michael S.; Renn, Megan L.; Moore, Charity G.; Weiss, Patricia M.; Condle, Joseph P.; Flickinger, Katharyn L.; Divecha, Ayushi A.; Coppler, Patrick J.; Sequeira, Denisse J.; Lang, Eddy S.; Higgins, J. Stephen; et al.
Abstract: Background : Fatigue training may be an effective way to mitigate fatigue-related risk. We aimed to critically review and synthesize existing literature on the impact of fatigue training on fatigue-related outcomes for Emergency Medical Services (EMS) personnel and similar shift worker groups.Methods : We performed a systematic literature review for studies that tested the impact of fatigue training of EMS personnel or similar shift workers. Outcomes of interest included personnel safety, patient safety, personnel performance, acute fatigue, indicators of sleep duration and quality, indicators of long-term health (e.g., cardiovascular disease), and burnout/stress. A meta-analysis was performed to determine the impact of fatigue training on sleep quality.Results : Of the 3, 817 records initially identified for review, 18 studies were relevant and examined fatigue training in shift workers using an experimental or quasi-experimental design. Fatigue training improved patient safety, personal safety, and ratings of acute fatigue and reduced stress and burnout. A meta-analysis of five studies showed improvement in sleep quality (Fixed Effects SMD −0.87; 95% CI −1.05 to −0.69; p < 0.00001; Random Effects SMD −0.80; 95% CI −1.72, 0.12; p < 0.00001).Conclusions : Reviewed literature indicated that fatigue training improved safety and health outcomes in shift workers. Further research is required to identify the optimal components of fatigue training programs to maximize the beneficial outcomes.